Informe anual 2022 del IICA - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Following the approval of the proposed adjustments to its Medium-term Plan (MTP) for the period 2022-2026, the Inter-American Institute for Cooperation on Agriculture (IICA) focused its work on five work strategies geared towards; being an IICA of open doors; providing technical cooperation of excellence; fostering a leadership style that strengthens agrifood systems; carrying out efficient administrative management; and strengthening the Institute’s finances and establishing partnerships. This report summarizes IICA’s main achievements in 2022 within the framework of its seven technical cooperation programs, as well as those resulting from corporate management, which underpins all the Institute’s operations.